«Даўыткөл» суў сақлағышының қысқаша физика-химиялық ҳәм гидробиологиялық сыпатламасы - Алламуратова, Г.Б.; Хожабаева, Ш.К. (FAN va JAMIYAT, 2021)
The article presents the temperature and basic physical - chemical characteristics of reservois, as well data on biogenic masses and food resources of the Dautkul reservoir.